Determining the Appropriate use of 3 Phase 150 kV Transformer Oil Using the Fuzzy Method - Dina Maizana, MT; Moulando Tampubolon; Muhathir Muhathir; Muhammad Fadlan Siregar; Yanawati Yahya (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2024)
Transformer is electrical power equipment that functions to convert electrical energy from one voltage value to another through the action of a magnetic field. Transformers are important electrical equipment because they are directly connected to electricity transmission and distribution lines. The aim of this research is to analyze transformer oil and its suitability standards. The type of research used is quantitative research using the Dissolved Gas Analysis (DGA) method. The data obtained for this method will be calculated by applying Fuzzy Logic to map the problem or determine variables. The mapping results will then be calculated using Matlab as the result of mathematical data analysis in graph form.